Fragilolides A-Q, norditerpenoid and briarane diterpenoids from the gorgonian coral Junceella fragilis. Issue 17 (27th April 2017) - Cheng, Wei; Ji, Ming; Li, Xiaodan; Ren, Jinwei; Yin, Fuling; van Ofwegen, Leen; Yu, Siwang; Chen, Xiaoguang; Lin, Wenhan
Abstract: Chemical investigation of the gorgonian coral Junceella fragilis resulted in the isolation of a new norditerpenoid fragilolide A (1 ), sixteen new briarane diterpenoids fragilolides B-Q (2–17 ), together with frajunolides H and N, and three known norcembranoids scabrolide D, sinuleptolide and 5- epi -sinuleptolide. The structures of new compounds were determined on the basis of extensive spectroscopic analysis, including the experimental and calculated ECD data and single-crystal X-ray diffraction for the configurational assignments. The structure of fragilolide A featured an unprecedented 4, 13- and 7, 11-fused tetracyclic norcembranoid, while the biogenetic relationships of the briarane analogues were postulated. Frajunolide H exerted significant inhibition against a panel of tumor cell lines, and six briarane diterpenoids (3, 6, 8, 12, 16, and frajunolide N) exhibited the inhibitory effects against the HBeAg express of hepatitis B virus in HepAD38 cells. In addition, sinuleptolide and 5- epi -sinuleptolide exerted the effects to inhibit NO production in RAW264.7 macrophage cells, in addition to the activation of ARE and the inhibition of NF-κB expression. Graphical abstract: